STROKE AS A COMPLICATION OF COVID-19 INFECTION - Vieira da Silveira Santos, Daniela; Romaneto Marques, Grazielle; Franco de Almeida, Leonardo; Luisa de Souza Holanda, Anna; Henrique Leite Guedes, Idrys; Carlos de Oliveira Dutra, João (Health and Society, 2021)
The coronavirus disease, caused by the new coronavirus, more contagious than it´s predecessors, has relations with the cerebrovascular accident. The stroke continues to be a medical emergency and evidences show that the infection by COVID-19 is a risc factor. The present article intend to determinate how the COVID-19 can influenciate in a stroke. The studies used in this article were found at PubMed and SciELO databases in English, Portuguese and Spanish, in the year of 2020, with the keywords “COVID-19”, “stroke”, “neurology” and “SARS-CoV-2”.